427 CLINICAL CORRELATIONS OF IN VITRO SUSCEPTIBILITY OF AMPHOTERICIN B PLUS FLUCYTOSINE IN AIDS-ASSOCIATED CRYPTOCOCCAL MENINGITIS. Issue 1 (1st January 2007) - Celaya, A. K.; Sanchez, A.; Chang, N.; Brouwer, A. E.; Harrison, T. S.; Thomas, A. M.; Bauer, M.; Larsen, R. A.
Abstract : Purpose of the Study: Cryptococcal meningitis is often treated with a combination of amphotericin B and flucytosine (5-FC). Susceptibility of Cryptococcus neoformans to these drugs has not been correlated with outcome. In one large trial, there appeared to be little clinical benefit from the addition of 5-FC to amphotericin B. We have previously used isolates from patients treated with amphotericin B alone to determine the equivalent concentration of amphotericin B at which the in vitro response has the strongest association with the quantitative patient response after 14 days of treatment with amphotericin given at 0.7 mg/kg/d. We now report our evaluation of in vitro susceptibility in patients who received the combination of amphotericin B plus 5-FC. Methods Used: Sixteen patients entered in a trial conducted in Thailand were treated with amphotericin B at 0.7 mg/kg combined with 5-FC at 100 mg/kg daily for 14 days. Patient response was measured by the numbers of C. neoformans per mL of cerebrospinal fluid on day 14. Summary of Results: When comparing the predicted response to amphotericin B alone based on in vitro susceptibility testing, the patient response when 5-FC is added to the treatment regimen is better than the predicted response to amphotericin B alone in a large portion of persons with cryptococcal meningitis. Conclusions: In vitro susceptibility testing can provide clinicians with important information for use in considering the value of adding 5-FC to amphotericin B.